Assessment of the potential of the southern part of the Zidarovo ore field in southeast Bulgaria for prospecting of critical and strategic raw materials - Ivanov Ivan; Sachkov Dimitar; Ruskov Kalin; Panayotova Marinela (E3S Web of Conferences)
The work is dedicated to analysing the relative abundance of chemical elements, defined as critical and strategic in recent EU documents, in an area with historical mining known as Zidarovo ore field, and located in Southeast Bulgaria. Fife samples of river sediments from the southern tributaries of the River Fakiiska were studied in order to assess the geochemical potential of the upper cretaceous rocks in the catchments. Critical metals and metalloids have been identified, which are found in the studied area in concentrations higher than the corresponding Clarke number. The correlations of these companion elements with the possible main carrier metals have been studied and the presumed base metals - carriers revealed. The findings can be used as an initial step in creation of a complex geomorphological-geological model of the area, based on GIS.